Relaxation of excess minority carrier distribution in macroporous silicon - L. A. Karachevtseva; V. F. Onyshchenko (Хімія, фізика та технологія поверхні, 2018)
Relaxation of the excess minority carrier distribution in macroporous silicon structure was calculated using the finite difference method. The initial distribution of the excess minority carriers has two maxima after carrier generation by electromagnetic wavelength 0.95 ?m with small absorption depth. The first maximum of the initial distribution function is in macroporous layer, the second one is in monocrystalline substrate. Surface recombination leads to the diffusion of excess charge carriers to recombination centers and creates the non-homogeneity of the excess charge carrier distribution. A rapid maximum decrease of the excess carrier distribution function in a macroporous layer and near the boundary of a macroporous layer and monocrystalline substrate is found. The slow decrease of the distribution function in a monocrystalline substrate is evaluated. We observed one maximum of the excess minority carrier distribution after homogeneous carrier generation by electromagnetic wavelength 1.05 ?m with big absorption depth. The rate of change in the concentration of excess minority carriers decreases in time in macroporous silicon layer due to high recombination and increases due to diffusion to the surface of silicon substrate after generation by the electromagnetic wave 0.95 ?m with small absorption depth. The rate of change in the concentration of excess minority carriers decreases in time in the entire structure after generation by the electromagnetic wave 1.05 ?m with big absorption depth and small non-homogeneity.